2014
DOI: 10.1111/desc.12265
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of one's actions upon hidden objects and the development of search behaviour in 7‐month‐old infants

Abstract: Infants' understanding of how their actions affect the visibility of hidden objects may be a crucial aspect of the development of search behaviour. To investigate this possibility, 7-month-old infants took part in a two-day training study. At the start of the first session, and at the end of the second, all infants performed a search task with a hiding-well. On both days, infants had an additional training experience. The 'Agency group' learnt to spin a turntable to reveal a hidden toy, whilst the 'Means-End' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…In contrast to others who have documented transfer of knowledge between two tasks requiring the same motor actions on different objects, O'Connor and Russell (2015) documented transfer of knowledge between two tasks requiring not only different objects, but also different actions. They found that after being trained to bring a hidden toy into view by rotating a turntable, 7-month-olds were able to successfully solve the hiding-well search task.…”
Section: Transfer Of Knowledge In Means-end Problem Solvingcontrasting
confidence: 92%
See 4 more Smart Citations
“…In contrast to others who have documented transfer of knowledge between two tasks requiring the same motor actions on different objects, O'Connor and Russell (2015) documented transfer of knowledge between two tasks requiring not only different objects, but also different actions. They found that after being trained to bring a hidden toy into view by rotating a turntable, 7-month-olds were able to successfully solve the hiding-well search task.…”
Section: Transfer Of Knowledge In Means-end Problem Solvingcontrasting
confidence: 92%
“…This confirmed that infants’ increase in goal‐directed behavior during Toy Trials likely represented the emergence of intentionality in means‐end problem solving (Willatts, ). Manual exploration of the means object coupled with visual observation of the effects on the end object may help young infants to develop a means‐end concept, so they can conceive and implement a correct sequence of actions (Bower & Wishart, ; Diamond, ) and also acquire “insight into agency” as they begin understanding the possible consequences of their own actions (O'Connor & Russell, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations